Peningkatan Kekakuan Atap Galvalum Sinusiodal 1,8x0,81m, Tebal 0,25 mm dengan Lekukan Garis, Kapasitas 300 Lembar/Jam (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The main issue addressed in this study is the insufficient stiffness of a sinusoidal galvalum roof measuring 1.8 × 0.81 m with a thickness of 0.25 mm. The objective was to improve the roof’s stiffness so that it could adequately withstand rainwater weight, wind loads, and human loads. The production process involved parametric finite element simulations to optimize profile stiffness, selection of aluminum-coated steel (Galvalum) consisting of 55% aluminum and 45% zinc, and roll-forming a sinusoidal profile with a wave height and depth of 20 mm. Additional curved lines, 2 mm deep and 10 mm wide, were introduced at the wave peaks and valleys to enhance structural rigidity. The process also included cutting the roof to a length of 1.8 m, bending tests to evaluate stiffness improvement, specification and brand printing, and quality inspection. The resulting roof exhibited a stiffness increase of 38.6% compared with the conventional profile. Production costs were IDR 3,222 per sheet, with a manufacturing time of 12 seconds per sheet. These results indicate that the modified sinusoidal galvalum roof provides greater stiffness and better performance at a standard support spacing of 1.2 m.